Comparing Task-Based and Project-Based Learning to Enhance Student Engagement in Elementary Social Science Classrooms - Hamid, Khondokar Sabera (Journal of Integrated Elementary Education, 2025)
This study aims to investigate the varied effects of TBL and PjBL on engagement in primary social science classrooms, which are conducted in Dhaka, Bangladesh. Both are student-centered approaches and both are generally effective at the elementary level; however, there is a dearth of research comparing the effects of these two methods on students' cognitive, affective, and behavioral engagement in this specific classroom context. A qualitative research design was used for the study, and data were gathered through semi-structured interviews with eight teachers and observations in five Class Four Social Studies sections. The information gathered was thematically analyzed in relation to the emerging patterns of participation connected to TBL and PjBL. The findings suggest TBL promotes on-task behaviour with short-term task engagement, contributing to enhanced content knowledge and increased classroom compliance. On the contrary, PjBL supports deeper and longer engagement by students in that they get to be involved cognitively, affectively, and behaviorally in real tasks and working together. However, the autonomy that is a key component of PjBL brings along with it the need for teachers to provide guidance to students, who are concerned with their study time and study focus, for example. This result suggests that a blended approach, combining the structured framework of team-based TBL with directional creativity from the PjBL, may effectively cater to individual differences in learning styles. The findings from this study highlight the importance of a blend of both methods and offering teachers professional development that will equip them to use these hybrid designs effectively.